A median filtering circuit using clocked CMOS neuron inverters for implantable electronic medical devices - Eguchi, Kei; Wongjan, Anan; Julsereewong, Amphawan; Harada, Yujiro; Fujimoto, Kuniaki (My University, 2017)
In the past few years, implantable electronic medical devices are receiving much attention in the field of biomedical engineering. In the design of the implantable electronic medical devices, not only small size but also low power consumption are required to achieve long working-life. In this paper, we present a complementary metal oxide semiconductor (CMOS) median filtering circuit using clocked neuron CMOS inverters. The aim of this work is to develop a CMOS implementable preprocessing circuit realizing low power consumption for implantable electronic medical devices such as a retinal prosthesis system. By controlling the duty cycle of clock pulses in the clocked neuron CMOS inverters, the proposed median filtering circuit can suppress the through current of inverters. Therefore, the proposed circuit can realize smaller power consumption than conventional median filtering circuits. Moreover, without arithmetic logic circuits, the median filtering based on the binary search algorithm is achieved in the proposed circuit. Therefore, the proposed circuit can offer the simple circuit configuration. Concerning the proposed circuit, the operation principle and theoretical design method are discussed in detail. Furthermore, the effectiveness of the proposed circuit is confirmed by simulation program with integrated circuit emphasis (SPICE) simulations. The simulated results demonstrate that the proposed median filtering circuit can reduce about 37% power consumption from the conventional circuit using CMOS neuron inverters.
Keywords: Image processing; Implantable electronics; Median filtering circuits; Neuron CMOS inverters; Neuron MOSFETs